Report on the regional workshop on methods and indicators - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
Broad and intensive consultative processes were conducted in Malawi and Uganda from June 2001 – July 2002 aimed at identifying the content and shape of an initiative that would enable agricultural R&D organizations to contribute effectively to the fight against HIV/AIDS. These involved the preparation of background papers describing the state of knowledge on HIV/AIDS and agriculture and the state of the response by sector organizations, public and private. Think Tanks in both countries, bringing together a wide range of persons involved in agricultural R&D and in AIDS control and public health, drew on these papers to identify the critical gaps in knowledge and the priorities for action research to address them. Stakeholders then met and refined these priorities and recommended the establishment of national networks that would support a broad-based initiative in each country. Out of these processes were born HIV/AIDS and the Agriculture Sector Network (HASNET)-Uganda and HIV/AIDS and the Agriculture Sector Action Research Network (HASARNET)-Malawi. These are the founding members of the Regional Network on AIDS, Rural Livelihoods and Food Security (RENEWAL). Their joint purpose is to support institutional innovation contributing to the prevention and mitigation of AIDS’ impacts. More specifically, their objectives are:; To fill critical gaps in understanding of the links, in both directions, between HIV/AIDS on one side, and agricultural systems, food security and rural livelihoods on the other; To fill critical gaps in understanding of how agricultural policies and programs can contribute to prevention and/or mitigation of AIDS impact and how this knowledge can be used to support local responses; To enable agricultural research and development institutions to act on realistic priorities for responding to HIV/AIDS epidemic in partnership with at-risk and affected communities and institutions in other sectors.